Analisis Sistem Pengendalian Intern Pada Koperasi (Studi Kasus Pada Koperasi Mahasiswa Universitas X) - Suci Rahayu; Sarifatul Hoiriyah; Kana Kanari; Devi Aulia Rahmawati; Saprina Aulia; Abdul Basit; Gista Rismayani (LPPM Universitas Koperasi Indonesia, 2026)
This study aims to analyze the internal control system at the Student Cooperative (KOPMA) of X University using the COSO framework, grounded in Agency Theory proposed by Jensen & Meckling (1976) underpins this study by explaining the principal-agent relationship between cooperative members and management, where information asymmetry necessitates robust internal controls to limit opportunistic behavior. The research employs a qualitative approach with a case study design. Data were collected through in-depth interviews with two key informants Treasurer and Public Relations and direct observation on May 24, 2026. Data analysis was conducted using the Miles and Huberman interactive model. The results indicate that overall, the internal control system of Kopma has been implemented reasonably well. The control environment is established with a clear organizational structure, written SOPs, and a competency-based recruitment mechanism. Risk assessment is conducted through weekly reconciliation and biweekly evaluation meetings. Control activities are implemented through tiered authorization and transaction evidence verification, although the the segregation of authorization and recording functions has not been fully optimized. Information and communication operate through weekly and monthly reporting, yet digitalization remains limited. Monitoring is carried out at multiple levels, ranging from daily to annual through the Annual Members' Meeting (RAT). This study concludes that Kopma X has implemented most internal control components according to the COSO framework, with the need for improvement in the segregation of functions and digitalization of reporting systems.